Integrasi Nilai-nilai Multikultural dalam Pembelajaran Pendidikan Agama Islam (PAI) - Fita Mustafida (Jurnal Pendidikan Islam Indonesia, 2020)
The existence of various cultures and diversity in society influences changes in the education system which is more directed at the principles of openness (inclusivism) and tolerance. Multicultural Islamic Education is an option in growing harmony and social relations in instilling multicultural values ​​in students. On this basis, this study seeks to describe multicultural values ​​and how to integrate those values ​​into learning. The location of the study was conducted at Sekolah Dasar Taman Harapan in Malang, known as a multicultural school, with qualitative research using a case study research design. The results of the study show that multicultural values ​​that grow and develop in Sekolah Dasar Taman Harapan include tolerance, togetherness, and love for peace. While the integration of multicultural values ​​in Islamic Education learning is carried out through the integration of multicultural values ​​in material, methods and learning media that are based on multicultural values.